IV Conference Ia ValSe-Food CYTED and VII Symposium Chia-Link 2022
DOI: 10.3390/blsf2022017005
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Hydrothermally Treated Flours in Gluten-Free Doughs

Abstract: This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https:// creativecommons.org/licenses/by/ 4.0/).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Heat-moisture treatment (HMT) is one such technique that has been explored for modifying the functional properties of flours. This method exposes flours to controlled heat and moisture conditions, altering the starch granular structure [10]. Recent studies have indicated that HMT can enhance the antioxidant profile of flours, promoting the liberation and availability of bound phenolic compounds [11].…”
Section: Introductionmentioning
confidence: 99%
“…Heat-moisture treatment (HMT) is one such technique that has been explored for modifying the functional properties of flours. This method exposes flours to controlled heat and moisture conditions, altering the starch granular structure [10]. Recent studies have indicated that HMT can enhance the antioxidant profile of flours, promoting the liberation and availability of bound phenolic compounds [11].…”
Section: Introductionmentioning
confidence: 99%